The Role of The Head of Madrasah in Improving Discipline of Educators in Paciran Lamongan - Muh. Hasyim Rosyidi; Fahrur Rosikh (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
The role of the head of the madrasa in the organization is needed to bring the organization to the goals that have been set. Improving teacher work discipline is a matter that will determine the success of school/madrasah institutions because it is from teachers that changes in the field of education will be achieved. The teacher factor determines the formation of quality students. Therefore, the role of the madrasa principal is needed in order to help teachers become more professional. This study uses a qualitative approach. Data was collected by using interviews, observation, and documentation techniques. While the data analysis technique, the researcher used data reduction, data presentation, and conclusion drawing. The results showed that: (1) The role of the head of the madrasa in improving the discipline of the teaching staff in Paciran Lamongan is a) the head of the madrasa as an educator (providing guidance and guidance to teachers), b) As a manager (through training and workshop), c) As an administrator (taking part in administrative matters), d) as a supervisor (providing direct or indirect supervision), e) as a leader (continuing to monitor and evaluate teachers), f) as an innovator (in meetings asking teachers to analyze policies or programs that need to be developed), g ) as a motivator (always giving encouragement, reminding and giving advice to teachers.